Exploring the experiences and challenges in managing type 2 diabetes among adults in Harare, Zimbabwe – a grounded theory study - Chirewa, Blessing M.; Nyashanu, Mathew; Barnard, Adam (International Journal Of Community Medicine And Public Health, 2026)
Background: The global increase in type 2 diabetes is particularly pronounced in low-income countries such as those in Sub-Saharan Africa, where the consequences are more severe. Fragile healthcare systems, shortages of healthcare workers, and poor patient disease management aggravate this trend. Understanding patients' experiences and difficulties is essential for developing evidence-based, patient-centered interventions from their perspective. This study aims to explore the experiences and challenges faced by patients with type 2 diabetes who are receiving care at community pharmacies in Harare, Zimbabwe. Method: Twenty-nine semi-structured interviews were conducted with individuals with type 2 diabetes who were recruited from community pharmacies using purposive and theoretical sampling. All interviews were audio-recorded and transcribed by the main researcher. Results: The study highlighted three main themes reflecting participants’ experiences with managing type 2 diabetes: striving to adjust; receiving social support; and feeling a loss of self-identity. Participants also pointed out the difficulties of living with the condition, including facing financial constraints, encountering societal stigma, and enduring negative emotions. For many, these emotional and financial struggles deeply challenged their resolve to manage the disease. Conclusion: Understanding the experiences and challenges faced by patients with type 2 diabetes from their perspective helps healthcare providers better grasp their needs, concerns, and fears. This understanding enables more person-centred support for self-management. Given that socioeconomic status greatly influences diabetes management, urgent policy changes are needed to lessen financial burdens, especially for low-income populations at greater risk as diabetes prevalence rises.